Microcontroller Based Automatic Power Factor Correction System - Harish Ravindran; Lilywati Bakar (Progress in Engineering Application and Technology, 2026)
This project shows how to make an Automatic Power Factor Correction (APFC) device based on a microcontroller by using the Arduino. The goal is to raise the power factor in single phase inductive loads by using relay modules to instantly switch capacitor banks based on voltage and current readings taken in real time. The ZMPT101B voltage sensor and the ACS712 current sensor are used by the system to find the change in phase between the voltage and current waves. This information is sent to a program written in the Arduino IDE, which uses it to figure out the power factor and take appropriate action when it drops below a certain level. The results show that the system does a good job of increasing the power factor, which lowers energy waste and raises efficiency. This small, cheap, and expandable system is perfect for small scale commercial and home uses where correcting the power factor is important.